Fatores associados ao acesso aos serviços de saúde na concepção de cuidadores de crianças - da Consolação Campos Ribeiro , Liliane; Letícia Ramos-Jorge, Maria; Lunardi Rocha , Regina (Revista Vozes dos Vales: Publicações Acadêmicas, 2014)
The aim of the present study was to evaluate factors related to health services and families associated with the access of children aged from zero to six years, in relation to type of health service of choice. A cross-sectional study was performed of a random stratified sample of 384 parents and/or guardians of children registered with five family health teams. Information was gathered using the Primary Care Assessment Tool (PCATool), created and validated in Brazil. Descriptive and univariate analysis and multiple logistic regression were performed, using a p<0.05 level of significance. In terms of access it was found that the majority of individuals interviewed identified family health teams as a regular source of health care for children (77.6%). There was no significant difference between reception/access to family health care in terms of the type of organization of the service. In conclusion, the present study found that the social conditions of families most affected reception/access to family health care.